Validating Technological Innovation The Introduction and Implementation of Onscreen Marking in Hong Kong - Coniam, David; Falvey, Peter (Springer Nature Singapore : Imprint: Springer, 2016)
This book discusses Hong Kong's use of onscreen marking (OSM) in public examinations. Given that Hong Kong leads the way in OSM innovation, this book has arisen from a recognised need to provide a comprehensive, coherent account of the findings of various separate but linked validation studies of onscreen public examinations in Hong Kong. The authors discuss their experience of the validation process, demonstrating how high-stakes innovation should be fully validated by a series of research studies in order to satisfy key stakeholders.